(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Shrimp paste is a popular traditional fermented seafood product and is used in cooking as a food seasoning. The unique taste and aromatic compounds of shrimp paste are made from the degradation of shrimp protein by salt-tolerant microorganisms. This study aims to compare the physicochemical composition and antioxidant activity content among different brands of shrimp paste at the local market. Four different samples of shrimp paste were labelled as SP1, SP2, SP3 and SP4. Sample SP1 showed the highest protein content (35.22 %) while sample SP4 contained the lowest protein (18.34 %). Sample SP4 showed significantly the highest moisture and ash content which were 39.25 % and 57.46 % respectively. The highest titratable acidity for sample SP4 (1.63 %) was significant in with accordance of high salinity content in shrimp paste. Sample SP1 was significantly higher (p